Néo-pentecôtisme à l’île de La Réunion : la revanche du Sud - Valérie Aubourg (Territoire en Mouvement)
Because they only consider as baptised adults having professed their faith following a spiritual experience of conversion, Pentecostal groups tend to be playing a role in pushing aside the traditional model of religious implantation. With them, religion is no longer consubstantial with territory.In Reunion Island, our research concerning historical Pentecostalism confirms this analysis. However, since 1983, a new form of Pentecostalism favouring the birth of autonomous churches (present mostly in the southern part of the island) has been spreading throughout the overseas department. This religious effervescence is set on the occasion of a reaffirmation of identity that reasserts the value of cultural elements peculiar to creole society at the expense of agents and practices bearing the seal of the Metropole. The fact that these movements thrive leads to the establishment of a new 'Pentecostal soil'. This soil leans on a set of specific features resulting, among other things, from the history of the agricultural structures in the southern insular region. This history, on the one hand is characterised by a mindset more independent than that of the North, and on the other hand it is based on an imbalance between a developed North and an underdeveloped South.